Highly potent host external immunity acts as a strong selective force enhancing rapid parasite virulence evolution. (25th April 2017) - Rafaluk, Charlotte; Yang, Wentao; Mitschke, Andreas; Rosenstiel, Philip; Schulenburg, Hinrich; Joop, Gerrit
Summary: Virulence is often under selection during host‐parasite coevolution. In order to increase fitness, parasites are predicted to circumvent and overcome host immunity. A particular challenge for pathogens are external immune systems, chemical defence systems comprised of potent antimicrobial compounds released by prospective hosts into the environment. We carried out an evolution experiment, allowing for coevolution to occur, with the entomopathogenic fungus, Beauveria bassiana, and the red flour beetle, Tribolium castaneum, which has a well‐documented external immune system with strong inhibitory effects against B. bassiana . After just seven transfers of experimental evolution we saw a significant increase in parasite induced host mortality, a proxy for virulence, in all B. bassiana lines. This apparent virulence increase was mainly the result of the B. bassiana lines evolving resistance to the beetles' external immune defences, not due to increased production of toxins or other harmful substances. Transcriptomic analyses of evolved B. bassiana implicated the up‐regulation of oxidative stress resistance genes in the observed resistance to external immunity. It was concluded that external immunity acts as a powerful selective force for virulence evolution, with an increase in virulence being achieved apparently entirely by overcoming these defences, most likely due to elevated oxidative stress resistance.